Development of the Conceptual Approach to the Content of the Internal Financial Audit System in the Public Administration Sector - A. S. Pavlova (Учёт. Анализ. Аудит, 2024)
The article analyzes theoretical approaches to the elemental composition of the internal financial audit system (hereinafter — IFA) in the public administration sector. The development of internal financial audit, in particular the creation of sufficient methodological support for internal financial audit, is considered as a basis for improving the quality of budget process management and increasing the efficiency of budget expenditures. The purpose of the study is to solve the scientific problem of expanding the internal financial audit in the public sector methodological tools, which is essential for the development of the public finance management theory and improving the budget expenditures efficiency. The information basis was the normative legal acts, which regulate the organization and implementation of the internal financial audit, the international organizations documents in the field of internal audit, the domestic researchers’ works in the field of internal financial audit and internal audit. The methodological basis of the work is formed on the scientific cognition general methods (collecting data about the research object, comparing approaches to categorizing the research object, processing data through analysis, synthesis, generalization, grouping and classification). The scientific novelty of this study lies in the improvement of methodological tools for internal financial auditing in the public administration sector, which is crucial for the development of the public financial management theory and for improving the budgetary expenditures efficiency. Based on the data of the national scientific school, the article clarifies and theoretically substantiates the elements of the internal financial audit system in the public administration sector. The conceptual approach proposed by this study can be applied in the public administration sector organizations with minor adaptations. The results of the study are intended for a wide range of readers, including chief administrators and administrators of budgetary funds in the internal financial audit organization and implementation, the Ministry of Finance of the Russian Federation in improving the internal financial audit methodology.